Adult Literacy and Weak Readers in PIAAC Cycle 1 - Rammstedt, Beatrice [Verfasser]; Gauly, Britta [Verfasser]; Zabal, Anouk [Verfasser] (Beltz Juventa, 2021)
"The 'Programme for the International Assessment of Adult Competencies' (PIAAC), which was initiated by the Organisation for Economic Co-operation and Development (OECD), assesses key skills of the adult population in an internationally comparable way. Over 35 countries with quite different degrees of economic development participated in the three rounds of the first cycle of PIAAC. This paper gives an overview of the average adult literacy skills by country and across countries and discusses the results from a German perspective. Furthermore, it explores how certain macro-economic indicators relate to the participating countries’ average adult literacy skills. PIAAC also provides information on adults with very low levels of literacy, thus enabling us to examine this group – the weak readers – more closely. Here too, we compare the proportion of weak readers across countries and examine how it relates to key country characteristics. In addition, we investigate which individual characteristics are associated with low reading skills. The paper concludes with a preview of the upcoming second cycle of PIAAC, which promises to yield additional and enhanced high-quality international data for further analyses." (Author's abstract, BIBB-Doku)

"Das 'Programme for the International Assessment of Adult Competencies' (PIAAC) wurde von der Organisation für Entwicklung und wirtschaftliche Zusammenarbeit (OECD) entwickelt, um die grundlegenden Kompetenzen der erwachsenen Bevölkerung in verschiedenen Ländern international vergleichend abzubilden. Am ersten Zyklus von PIAAC nahmen über 35 Länder teil, die deutlich in ihrer wirtschaftlichen Entwicklung variieren. In diesem Artikel vergleichen wir die durchschnittliche Lesekompetenz der teilnehmenden Länder und reflektieren sie vor dem Hintergrund der unterschiedlichen wirtschaftlichen Entwicklung der Länder. Im Fokus der Analysen stehen Personen mit äußerst geringen Lesekompetenzen (schwache Lesende). Wir kontrastieren den Umfang der schwachen Lesenden über die Länder und untersuchen welche Makro-Indikatoren als Erklärungen für die Länderdifferenzen herangezogen werden können. Zusätzlich analysieren wir welche individuellen Merkmale mit geringen Lesekompetenzen zusammenhängen. Wir schließen mit einem Ausblick auf den kommenden zweiten Zyklus von PIAAC und dessen Innovationen." (Autorenreferat, BIBB-Doku)
Keywords: P 1.2 Erwachsene; 370; Erwachsener; Lesekompetenz; Einflussfaktor; Ökonomische Faktoren; Bruttoinlandsprodukt; Armut; Einkommenshöhe; Soziodemografische Faktoren; Alter; Geschlecht; Bildungsniveau; Muttersprache; Regressionsanalyse; Internationaler Vergleich; PIAAC